Behavioral determinants of retention in Indonesia’s national health insurance: a retrospective cohort study of informal workers - Syarif Rahman Hasibuan (Universitas Gadjah Mada, 2026)
Purpose: This study aimed to examine factors influencing enrollment continuity among self-enrolled members of Indonesia’s National Health Insurance (JKN) from 2018 to 2023. Methods: This study used data from BPJS Kesehatan, a longitudinal cohort of 124,486 active members in 2018, and followed up to assess participation status in 2023. Results: About 38.1% of participants became inactive, and those who had never used primary or hospital care were over four times as likely to drop out (OR 4.27; 95% CI 4.25–4.28). Inactivity was also more common among rural residents and members living outside the Java–Bali region. Conclusion: These findings suggest a risk of adverse selection, where low-utilizers exit while high-need members remain. Retention depends not only on affordability but also on perceived value, highlighting the need for preventive outreach, service quality improvements, and simplified administrative processes.